2011
DOI: 10.1016/j.biopsych.2010.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Ketamine on the Experience of Illusory Body Ownership

Abstract: BackgroundOur sense of body ownership is profound and familiar, yet it may be misleading. In the rubber-hand illusion, synchronous tactile and visual stimulation lead to the experience that a rubber hand is actually one's own. This illusion is stronger in schizophrenia. Given the evidence that ketamine, a noncompetitive N-methyl-D-aspartate antagonist reproduces symptoms of schizophrenia, we sought to determine whether the rubber-hand illusion is augmented by ketamine.MethodsWe studied 15 healthy volunteers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 42 publications
8
66
1
2
Order By: Relevance
“…These findings share some similarity to those of the present study in that either an administered drug (Morgan et al, 2011) or already present biases in multisensory integration (predisposition to OBEs) can lead to an increased tendency to accept ownership of an illusory limb. This occurs even when there is contradiction between sensory information (the asynchronous condition).…”
Section: Skin Conductance Responses (Scrs)supporting
confidence: 89%
See 1 more Smart Citation
“…These findings share some similarity to those of the present study in that either an administered drug (Morgan et al, 2011) or already present biases in multisensory integration (predisposition to OBEs) can lead to an increased tendency to accept ownership of an illusory limb. This occurs even when there is contradiction between sensory information (the asynchronous condition).…”
Section: Skin Conductance Responses (Scrs)supporting
confidence: 89%
“…For example, Morgan et al, (2011) showed that the strength of the RHI is augmented by ketamine, a substance known to replicate the symptoms of psychosis and produce an altered sense of self.…”
Section: Skin Conductance Responses (Scrs)mentioning
confidence: 99%
“…112 Furthermore, Ketamine augments experience of the rubber hand illusion, the spurious sense of ownership of a prop-hand if the hand is stroked at the same time as one's own hand. 113 People on ketamine get the illusion more strongly and they experience it even in a control condition when the real and rubber hands are stroked asynchronously. 113 Patients with schizophrenia 114 and chronic ketamine abusers show the same excessive experience of the illusion in the synchronous and asynchronous conditions.…”
Section: Predictive Coding Of Self and Othermentioning
confidence: 99%
“…Another useful approach for dissociating constructs of corporeal awareness is to administer a drug with well-defined actions on the central nervous system (e.g., Morgan et al 2010). Dexamphetamine is a relatively safe and effective drug that selectively releases dopamine, noradrenaline and, to a lesser extent, serotonin (Philips et al 1982;Hegadoren et al 1994).…”
Section: Introductionmentioning
confidence: 99%